Spooky ballet! : Agent Amelia - Broad, Michael (London : Andersen Press, 2009)
Young Amelia, a secret agent, investigates a class of entranced ballet students, a scarecrow that can control crows, and a librarian whose work on the school library's computers seems to turn students into robots.
The case of the spooky ballet -- The case of the whistling scarecrow -- The case of the gobbledygook books.
Keywords: Spies -- Fiction; Ballet dancing -- Fiction; Scarecrows -- Fiction; Computer crimes -- Fiction